Of Mice and Men, de John Steinbeck (Cadernos de Literatura em Tradução, 2021)
The aim of this paper is to propose a translation into Brazilian Portuguese of the first excerpt in John Steinbeck’s literary work Of mice and men. The excerpt to be translated contains the voice of the narrator, in standard American English, as opposed to the voice of the two main characters in the story, Lennie and George, conceived as a dialectal variant with features of orality often marked by informal words and/or use of non-standard spelling and syntax. The translation aimed at attempting to maintain in Brazilian Portuguese the opposition between the narrator’s voice, in standard American English, and the orality marks of the characters’ speeches in an attempt to keep verisimilitude with the oral speech of Brazilian Portuguese speakers, as well as the internal verisimilitude with the orality contained in the characters’ speeches.